2017
DOI: 10.1080/14445921.2017.1299453
|View full text |Cite
|
Sign up to set email alerts
|

Valuers’ receptiveness to the application of artificial intelligence in property valuation

Abstract: Studies have shown that the level of valuation inaccuracy in Nigeria is higher than the international acceptable standard. This may be linked to the preference for traditional valuation approaches in practice. This study investigate the readiness of Nigerian valuers to adopt the artificial intelligence (AI) appraisal techniques, which have proven to be reliable and accurate in other property markets, both in theory and in practice. A cross-sectional study was conducted via a web-based questionnaire survey to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
2
10
0
1
Order By: Relevance
“…This conforms to the findings of Abidoye and Chan (2017b), who found that the professional bodies and educational institutions are partly responsible for the lack of awareness and adoption of the advanced valuation methods by valuers in Nigeria.…”
Section: Resultssupporting
confidence: 91%
“…This conforms to the findings of Abidoye and Chan (2017b), who found that the professional bodies and educational institutions are partly responsible for the lack of awareness and adoption of the advanced valuation methods by valuers in Nigeria.…”
Section: Resultssupporting
confidence: 91%
“…This suggests that most of the valuers practising in the Australian property market are male. This is the similar gender mix reported about real estate professionals in previous studies by Mooya (2015) (South Africa), Wilkinson et al (2018) (Australia), and Abidoye and Chan (2017) (Nigeria), among others. This suggests that the real estate profession is dominated by men.…”
Section: Resultssupporting
confidence: 88%
“…Also, the Chi-square ( χ 2 ) test was conducted to examine the statistical relationship that exists between valuers' profile and factors that affect property valuation inaccuracy in Australia. A similar approach was adopted in previous studies (see, Abidoye and Chan, 2017 among others). In order to ensure the reliability, validity and consistency of the collected data, the Cronbach's alpha test was performed.…”
Section: Data and Research Methodologymentioning
confidence: 99%
“…They will be able to take advantage of the services sold to them by the largest players in the industry. Technological innovation will therefore bring radical changes to the current structure of the professional sector of evaluators (Abidoye and Chan, 2017).…”
Section: Avms Vs Hedonic Modelsmentioning
confidence: 99%